Efficacy Of Various Insecticides Against Tomato Leaf Miner, Tuta Absoluta, In Egypt (Applied Biological Research, 2015)
Tuta absoluta has recently become one of the most devastating pests of  tomato in Egypt. In this study, field experiments were conducted during  two summer seasons (2012 and 2013) to determine the effectiveness of  four insecticides, abamectin 152.4 g L-1 + thiamethoxam 33.2 g L-1  (Agriflex 18.6% SC), chlorpyrifos (Lirifos 48% EC), spinosad (Tracer  24% SC) and imidacloprid (Admire 20% SC), in controlling T. absoluta  in tomato. These insecticides were found effective in reducing T. absoluta infestation in both the seasons. Spinosad proved most promising and  caused 98.6% reduction in T. absoluta infestation in comparison of 62.8  and 54.8% by abamectin + thiamethoxam and chlorpyrifos, respectively.  Imidacloprid was least effective with infestation reductions of 9.3%.
Keywords: Field evaluation; insecticides; pest management; tomato; Tuta absoluta